Three new records for the flora of Turkey: Campanula lyrata subsp. icarica (Campanulaceae), Erysimum aureum (Brassicaceae) and Stachys benthamiana (Lamiaceae) - Özdöl, Tuğkan; Güner, Özal; Sefali, Abdurrahman; Akçi̇çek, Ekrem; Di̇rmenci̇, Tuncay; Yildirim, Hasan (Phytotaxa, 2022)
N/A